High-Strength 3D-Ordered Ceramic-Gel Composite Electrolytes Enable Highly Stable Sodium Metal Batteries at − 20 to 60 °C - Shen, Liying; Hu, Chuyan; Huang, Zhenhui; Yang, Jiarui; Jia, Yanwei; Zhao, Yufeng; Berger, Rüdiger; Liu, Qiang; Zhou, Yu (Nano-Micro Letters, 2026)
Ceramic-gel composite electrolytes (CGEs) attract significant attention as solid-state electrolytes (SSEs) for sodium metal batteries owing to their favorable ionic conductivity and interfacial compatibility. However, conventional CGEs generally feature insufficient mechanical strength and consequent uncontrollable dendrite growth, remaining long-standing fundamental challenges that severely limit practical applications. Herein, this study presents a high-strength CGE that enables efficient stress transfer, achieving a compressive strength of 20.1 MPa (20 times higher than conventional gel electrolytes), while maintaining excellent ionic conductivity and effectively suppressing sodium dendrites. The 3D-Na3Zr2Si2PO12 framework further serves as a thermal barrier, imparting the CGE with superior flame retardancy. Additionally, Na/CGE/NVP-K0.05 cells exhibit 75.9% capacity retention after 10,000 cycles at 5C (25 °C) and deliver 78.5 mAh g−1 at 30C (60 °C). Remarkably, the CGE exhibits excellent low-temperature adaptability, retaining nearly 100% capacity at –20 °C. These results highlight a viable strategy for designing safe and high-performance solid-state sodium metal batteries toward practical deployment. Highlights: 1 A high-strength ceramic-gel electrolyte enables efficient stress transfer, achieving a compressive strength of 20.1 MPa (20 times that of conventional gel electrolytes) while maintaining excellent ionic conductivity and effectively suppressing sodium dendrite growth. 2 The Na3Zr2Si2PO12 framework acts as a thermal barrier, imparting the ceramic-gel composite electrolytes with superior flame retardancy and maintaining structural integrity after 30 s of burning. 3 The structural–functional integration ensures efficient Na⁺ conduction (3.37 × 10−3 S cm−1) and stable performance from − 20 to 60 °C.